ACNE, ISOTRETINOIN, AND PSYCHIATRIC ADVERSE EVENTS: MONITORING PRIORITIES BASED ON FAERS ANALYSIS (2005–2025) (Western European Journal of Medicine and Medical Science, 2025)
Introduction and Objective Isotretinoin remains one of the most effective medications for the treatment of severe acne, but its potential impact on patients' mental health is controversial. Despite numerous studies, outside of depression and suicidal behavior, it's unclear which psychiatric adverse events (AEs) require priority monitoring. Acne, Isotretinoin, and Depression: What Patients Need to Know. Isotretinoin is one of the most effective treatments for moderate to severe acne. It helps where creams, antibiotics, and cosmetic procedures fail. However, it remains a source of considerable concern, particularly related to the potential risk of depression.